Reimagining Divine Presence: Interpretation Of Matthew 28:20b And The Song “O Mawu Rendingane” As The Voice Of Sangihe Community - Adilang, Ryanto; Kalintabu, Heliyanti; Udang, Frety Cassia; Tombokan, Tifany Fergie (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
Living life on earth as a human being is certainly not free from various challenges and problems. In our fragility, humans will always depend on God to prevent collapse when faced with life's challenges. For this reason, God's presence is crucial in human life and faith. Matthew 28:20B presents Jesus' narrative about His promise of presence to his disciples. Therefore, this study aims to highlight this promise of presence in a dialogue with the voices of the local community through the song "O Mawu Rendingane." This research was conducted using a qualitative method with a hermeneutic approach. Historical hermeneutics was chosen to analyze the biblical text, namely Matthew 28:20B. In the dialogue with the song "O Mawu Rendingane," Choan-Seng Song's Story Theology was chosen as the most appropriate theory. This research is expected to uncover new ways to read and understand Jesus' promise of presence contained in Matthew 28:20B. Furthermore, it is hoped that this dialogue will broaden the meaning of Matthew 28:20B.